Method for improving specific capacity and stability of aqueous sodium-ion battery
By adding specific additives to the sulfate system electrolyte of aqueous sodium ion batteries, the problem of low electrochemical stability window is solved, the specific capacity and stability of the battery are improved, and a wider selection of positive and negative electrode materials and higher ionic conductivity.
Patent Information
- Application Number
- CN202411703907.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-21
AI Technical Summary
The electrochemical stability window of aqueous sodium ion batteries is low, resulting in limited selection of positive and negative electrode materials, and the battery exhibits low energy density, low cycle life and safety risks.
Add MgSO4 additive, MgSO4-K2SO4 mixed additive or MgSO4-(NH4)2SO4 mixed additive to the sulfate system electrolyte to broaden the electrochemical stability window, inhibit the decomposition of water, increase the selection range of positive and negative electrode materials, and enhance the electrolyte solution ionic conductivity.
It effectively improves the specific capacity and stability of aqueous sodium ion batteries, expands the electrochemical stability window, enhances the cyclic stability of the battery, and reduces production costs.
Smart Images

Figure HDA0005154064790000011 
Figure HDA0005154064790000012 
Figure HDA0005154064790000021
Abstract
Description
Technical Field
[0001] The invention relates to a method for improving the specific capacity and stability of an aqueous sodium ion battery, and belongs to the technical field of aqueous sodium ion batteries. Background Art
[0002] Lithium-ion batteries are widely used due to their significant energy density, high efficiency, and long cycle life. However, due to the limited reserves of lithium resources, lithium-ion batteries cannot support the development of both electric vehicles and large-scale energy storage. Therefore, new energy storage battery technologies must be developed to support their sustainable development. In recent years, sodium-ion batteries, which have the same working principle and similar battery components as lithium-ion batteries, have attracted widespread attention due to their advantages such as abundant sodium resources, low cost, and good overall performance.
[0003] So far, organic electrolytes are mainly used. However, the use of organic electrolytes can easily lead to heat accumulation or external collisions, which can easily cause battery safety problems, and in severe cases, fire and explosion. Therefore, it is safer to use aqueous electrolytes and they have the advantages of high ionic conductivity, simple operation and low cost. However, due to the electrolysis of water (the release of hydrogen and oxygen), the thermodynamic stability window of water is only 1.23V. Although the actual range may reach 1.8V due to the limitation of reaction kinetics, this also greatly limits the selection of positive and negative electrode materials for aqueous sodium ion batteries. It is easy for hydrogen evolution reaction to occur on the negative electrode side and oxygen evolution reaction to occur on the positive electrode side. The assembled aqueous full batteries often have low voltage platforms, low energy density and poor cycle life, which greatly limit the development and application of aqueous sodium ion batteries.
[0004] At present, concentrated aqueous electrolytes can greatly broaden the electrochemical stability window and improve cycle stability. Whitacre et al. explored the effect of electrolyte concentration on the performance and stability of NaTi2(PO4)3 / Na0.44MnO2 aqueous sodium ion batteries. The results showed that at 1.5C, the capacitance increased by 38% by increasing the concentration of NaClO4 solution from 1M to 5M. The voltage window can also be expanded and the cycle stability improved by adding additives to the aqueous electrolyte. Wu et al. reported an electrolyte with polyethylene glycol as a molecular crowding agent, whose electrochemical window was widened to 3.2V. However, these measures will lead to a series of problems such as high production costs and low ionic conductivity. Therefore, it is particularly necessary to find a simple, easy and high ionic conductivity method to broaden the electrochemical window of aqueous electrolytes. Summary of the invention
[0005] In view of the problem of low electrochemical stability window of existing aqueous electrolytes, the present invention proposes a method for improving the specific capacity and stability of aqueous sodium ion batteries. By adding MgSO4 additives, MgSO4-K2SO4 mixed additives or MgSO4-(NH4)2SO4 mixed additives to sulfate system electrolytes, it is beneficial to improve the electrochemical stability window of aqueous electrolytes, inhibit the decomposition of water, and expand the selection range of positive and negative active materials, and have higher ionic conductivity; it can effectively improve the specific capacity and stability of aqueous sodium ion batteries.
[0006] A method for improving the specific capacity and stability of an aqueous sodium ion battery, using a sulfate system electrolyte, wherein the sulfate system electrolyte comprises sodium sulfate, an additive and deionized water, wherein the additive is MgSO4, a MgSO4-K2SO4 mixed additive or a MgSO4-(NH4)2SO4 mixed additive;
[0007] The sodium sulfate concentration in the sulfate system electrolyte is 2-2.3 mol / L.
[0008] Preferably, when the additive is MgSO4, the concentration of the additive MgSO4 is 0.8-1.24 mol / L.
[0009] Preferably, when the additive is a MgSO4-K2SO4 mixed additive, the concentration of the additive MgSO4 is 1 to 1.24 mol / L, and the concentration of K2SO4 is 0.46 to 0.5 mol / L.
[0010] Preferably, when the additive is a MgSO4-(NH4)2SO4 mixed additive, the concentration of the additive MgSO4 is 1 to 1.24 mol / L, and the concentration of (NH4)2SO4 is 0.46 to 0.5 mol / L.
[0011] The electrochemical stability window of the sulfate system electrolyte is 3.2-3.67V, and the conductivity value is 77.3-98.6mS / cm.
[0012] Preferably, the negative electrode material of the aqueous sodium ion battery is a titanium-based polyanion compound NaTi2(PO4)3 / C, and the positive electrode material is a vanadium-based polyanion compound Na3V2(PO4)3.
[0013] The mechanism of improving the specific capacity and stability of aqueous sodium ion batteries by the present invention is as follows: 2+ The strong interaction causes water molecules to tend to 2+ The original regular cross-linking structure between water molecules is destroyed, which weakens the strength of hydrogen bonds between water and water, thereby increasing the electrochemical window of the electrolyte. 2+ The radius is greater than Na+ Small, Na + and Mg 2+ During the discharge process, Mg can be embedded in the lattice to generate capacity. 2+ It is easier to insert into the lattice, resulting in an increase in capacity and voltage. 2+ It has a divalent nature, which means that each magnesium ion carries two positive charges. In the electrolyte, high-valent ions usually form stronger interactions with solvent molecules, resulting in a lower ion migration rate. This interaction reduces the number of free mobile ions and thus reduces conductivity. In ammonium sulfate and magnesium sulfate, K + and NH 4+ It has high solubility and conductivity, which can improve the conductivity of the electrolyte, thereby improving the performance of the battery. At the same time, potassium ion compounds help to form a stable solid electrolyte interface layer (SEI) on the electrode surface. The SEI layer can isolate electrons and ensure continuous ion transfer, inhibit excessive consumption of the electrolyte by side reactions, and thus improve electrochemical stability.
[0014] The beneficial effects of the present invention are:
[0015] (1) The present invention adds MgSO4 additive, MgSO4-K2SO4 mixed additive or MgSO4-(NH4)2SO4 mixed additive to the sulfate system electrolyte. The MgSO4 additive can destroy the hydrogen bond network of water, thereby expanding the electrochemical stability window to 3.51V. Due to the addition of the MgSO4 additive, the ionic conductivity decreases from 98.6mS / cm to 77.3-74.6mS / cm. The addition of the additive K2SO4 or (NH4)2SO4 can further destroy the hydrogen bond network of water, thereby further expanding the electrochemical stability window to 3.67V, thereby increasing the ionic conductivity of the electrolyte to 83.2-85.4mS / cm.
[0016] (2) The aqueous sodium ion full battery electrolyte of the present invention forms a solid electrolyte interface layer during the circulation process, thereby improving the structural stability and electrochemical performance of the positive and negative electrode materials in the sulfate system electrolyte, thereby enhancing the cycle stability of the aqueous sodium ion battery, and has low cost and simple operation; the sulfate system electrolyte added with MgSO4 additive, MgSO4-K2SO4 mixed additive or MgSO4-(NH4)2SO4 mixed additive, the full battery at 0.1Ag -1 At the current density, its first discharge capacity reaches 44.8~45.3mAhg -1 After 300 cycles, the specific capacity remains at 43.7-44.9 mAh g -1 , with high cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is a linear sweep voltammetry curve of the sulfate system electrolyte in Example 3;
[0018] Figure 2 The electrochemical performance test of the sulfate system electrolyte in Example 3;
[0019] Figure 3 is a linear sweep voltammetry curve of the sulfate system electrolyte in Example 4;
[0020] Figure 4 The electrochemical performance test of the sulfate system electrolyte in Example 4;
[0021] Figure 5 is the CV diagram of the sulfate system electrolyte in Example 4;
[0022] Figure 6 is a linear sweep voltammetry curve of the sulfate system electrolyte in Example 9;
[0023] Figure 7 This is the electrochemical performance test of the sulfate system electrolyte in Example 9. DETAILED DESCRIPTION
[0024] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.
[0025] Embodiment 1: A method for improving the specific capacity and stability of an aqueous sodium ion battery, using a sulfate system electrolyte, wherein the sulfate system electrolyte comprises sodium sulfate, an additive (MgSO4) and deionized water; the concentration of sodium sulfate in the sulfate system electrolyte is 2.3 mol / L, and the concentration of the additive (MgSO4) is 1 mol / L;
[0026] Taking the sulfate system electrolyte without MgSO4 as a reference and Ag / AgCl as a reference electrode, the electrochemical test was performed by linear sweep voltammetry. The electrochemical stability window of the sulfate system electrolyte without MgSO4 was about 3.25V, and its ion conductivity was 98.6mS / cm at room temperature; the electrochemical stability window of the sulfate system electrolyte with MgSO4 added in this embodiment was about 3.4V, and its ion conductivity was 80.3mS / cm at room temperature;
[0027] In this embodiment, the GCD curves of the positive and negative electrodes are tested by a three-electrode system, including a working electrode (the negative electrode active material is Na3V2(PO4)3, and the positive electrode active material is NaTi2(PO4)3 / C), a reference electrode (Ag / AgCl), a counter electrode (graphite carbon rod) and a sulfate system electrolyte. The working electrode includes a stainless steel current collector and a Na3V2(PO4)3 or NaTi2(PO4)3 / C material layer coated on the surface of the stainless steel current collector. The negative electrode Na3V2(PO4)3 material layer includes Na3V2(PO4)3 active material, a conductive agent (carbon black C65) and a binder (PTFE). The positive electrode NaTi2(PO4)3 / C material layer includes Na Ti2(PO4)3 / C active material, conductive agent (carbon black C65) and binder (PTFE); in terms of mass percentage, Na3V2(PO4)3 accounts for 70% of the negative electrode Na3V2(PO4)3 material layer, conductive agent (carbon black C65) accounts for 20%, and binder (PTFE) accounts for 10%; in terms of mass percentage, NaTi2(PO4)3 / C accounts for 80% of the positive electrode NaTi2(PO4)3 / C material layer, conductive agent (carbon black C65) accounts for 20%, and binder (PTFE) accounts for 10%; the weight of the Na3V2(PO4)3 material layer on the negative electrode stainless steel mesh is 3.5 mg, and the weight of the NaTi2(PO4)3 / C material layer on the positive electrode stainless steel mesh is 4 mg;
[0028] Sulfate electrolyte without MgSO4 additive, at 0.1Ag -1 At this current density, the first discharge specific capacity of the positive electrode is 67.42 mAh g -1 The third discharge specific capacity is 61.56 mAhg -1 The electrode dissolves and the specific capacity drops to 37.56 mAh g after the 15th discharge. -1 ; Sulfate system electrolyte with MgSO4 additive, at 0.1Ag -1 At this current density, the first discharge capacity of the positive electrode reaches 49.3 mAh g -1 The third discharge specific capacity is 50.2 mAhg -1 ; at 0.1Ag -1 At this current density, the first discharge capacity of the negative electrode reached 25.6 mAh g -1 .
[0029] Embodiment 2: A method for improving the specific capacity and stability of an aqueous sodium ion battery, using a sulfate system electrolyte, wherein the sulfate system electrolyte comprises sodium sulfate, an additive (MgSO4) and deionized water; the concentration of sodium sulfate in the sulfate system electrolyte is 2.2 mol / L, and the concentration of the additive (MgSO4) is 1.12 mol / L;
[0030] Taking the sulfate system electrolyte without MgSO4 as a reference and Ag / AgCl as a reference electrode, the electrochemical test was performed by linear sweep voltammetry. The electrochemical stability window of the sulfate system electrolyte without MgSO4 was about 3.25V, and its ion conductivity was 98.6mS / cm at room temperature; the electrochemical stability window of the sulfate system electrolyte with MgSO4 added in this embodiment was about 3.48V, and its ion conductivity was 79mS / cm at room temperature;
[0031] In this embodiment, the GCD curves of the positive and negative electrodes are tested by a three-electrode system, including a working electrode (the negative electrode active material is Na3V2(PO4)3, and the positive electrode active material is NaTi2(PO4)3 / C), a reference electrode (Ag / AgCl), a counter electrode (graphite carbon rod) and a sulfate system electrolyte. The working electrode includes a stainless steel current collector and a Na3V2(PO4)3 or NaTi2(PO4)3 / C material layer coated on the surface of the stainless steel current collector. The negative electrode Na3V2(PO4)3 material layer includes Na3V2(PO4)3 active material, a conductive agent (carbon black C65) and a binder (PTFE). The positive electrode NaTi2(PO4)3 / C material layer includes NaT i2(PO4)3 / C active material, conductive agent (carbon black C65) and binder (PTFE); in terms of mass percentage, Na3V2(PO4)3 accounts for 70% of the negative electrode Na3V2(PO4)3 material layer, conductive agent (carbon black C65) accounts for 20%, and binder (PTFE) accounts for 10%; in terms of mass percentage, NaTi2(PO4)3 / C accounts for 80% of the positive electrode NaTi2(PO4)3 / C material layer, conductive agent (carbon black C65) accounts for 20%, and binder (PTFE) accounts for 10%; the weight of the Na3V2(PO4)3 material layer on the negative electrode stainless steel mesh is 3.8mg, and the weight of the NaTi2(PO4)3 / C material layer on the positive electrode stainless steel mesh is 4.6mg;
[0032] In this embodiment, the sulfate electrolyte with MgSO4 additive is added at 0.1Ag -1 At this current density, the first discharge capacity of the positive electrode reached 50.42 mAh g -1 The third discharge capacity is 52.56 mAh g -1 ; at 0.1Ag -1 At this current density, the first discharge capacity of the negative electrode reaches 28 mAhg -1 .
[0033] Embodiment 3: A method for improving the specific capacity and stability of an aqueous sodium ion battery, using a sulfate system electrolyte, wherein the sulfate system electrolyte comprises sodium sulfate, an additive (MgSO4) and deionized water; the concentration of sodium sulfate in the sulfate system electrolyte is 2.1 mol / L, and the concentration of the additive (MgSO4) is 1.24 mol / L;
[0034] Using sulfate electrolyte without MgSO4 as reference and Ag / AgCl as reference electrode, electrochemical tests were performed by linear sweep voltammetry. Figure 1 As shown, the electrochemical stability window of the sulfate system electrolyte without adding MgSO4 is about 3.25V, and its ion conductivity at room temperature is 98.6mS / cm; the electrochemical stability window of the sulfate system electrolyte with MgSO4 added in this embodiment is about 3.51V, and its ion conductivity at room temperature is 77.3mS / cm;
[0035] In this embodiment, the GCD curves of the positive and negative electrodes are tested by a three-electrode system, including a working electrode (the negative electrode active material is Na3V2(PO4)3, and the positive electrode active material is NaTi2(PO4)3 / C), a reference electrode (Ag / AgCl), a counter electrode (graphite carbon rod) and a sulfate system electrolyte. The working electrode includes a stainless steel current collector and a Na3V2(PO4)3 or NaTi2(PO4)3 / C material layer coated on the surface of the stainless steel current collector. The negative electrode Na3V2(PO4)3 material layer includes Na3V2(PO4)3 active material, a conductive agent (carbon black C65) and a binder (PTFE). The positive electrode NaTi2(PO4)3 / C material layer includes NaT i2(PO4)3 / C active material, conductive agent (carbon black C65) and binder (PTFE); in terms of mass percentage, Na3V2(PO4)3 accounts for 70% of the negative electrode Na3V2(PO4)3 material layer, conductive agent (carbon black C65) accounts for 20%, and binder (PTFE) accounts for 10%; in terms of mass percentage, NaTi2(PO4)3 / C accounts for 80% of the positive electrode NaTi2(PO4)3 / C material layer, conductive agent (carbon black C65) accounts for 20%, and binder (PTFE) accounts for 10%; the weight of the Na3V2(PO4)3 material layer on the negative electrode stainless steel mesh is 3.4mg, and the weight of the NaTi2(PO4)3 / C material layer on the positive electrode stainless steel mesh is 3.8mg;
[0036] like Figure 2 As shown, in this embodiment, the sulfate electrolyte with MgSO4 additive added is -1 At this current density, the first discharge capacity of the positive electrode reached 51.33 mAh g -1 The third discharge capacity is 54.17 mAh g -1 ; at 0.1Ag-1 At this current density, the first discharge capacity of the negative electrode reaches 29 mAhg -1 .
[0037] Embodiment 4: A method for improving the specific capacity and stability of an aqueous sodium ion battery, using a sulfate system electrolyte, wherein the sulfate system electrolyte comprises sodium sulfate, an additive (MgSO4-K2SO4 mixed additive) and deionized water; the concentration of sodium sulfate in the sulfate system electrolyte is 2.3 mol / L, the concentration of the additive (MgSO4) is 1.24 mol / L, and the concentration of the additive (K2SO4) is 0.46 mol / L;
[0038] Using the sulfate electrolyte without MgSO4-K2SO4 as reference and Ag / AgCl as reference electrode, electrochemical tests were performed by linear sweep voltammetry. Figure 3 As shown, the electrochemical stability window of the sulfate system electrolyte without the addition of the MgSO4-K2SO4 mixed additive is about 3.25V, and its ion conductivity at room temperature is 98.6mS / cm; the electrochemical stability window of the sulfate system electrolyte with the addition of the MgSO4-K2SO4 mixed additive in this embodiment is about 3.67V, and its ion conductivity at room temperature is 85.4mS / cm;
[0039] In this embodiment, the GCD curves of the positive and negative electrodes are tested by a three-electrode system, including a working electrode (the negative electrode active material is Na3V2(PO4)3, and the positive electrode active material is NaTi2(PO4)3 / C), a reference electrode (Ag / AgCl), a counter electrode (graphite carbon rod) and a sulfate system electrolyte. The working electrode includes a stainless steel current collector and a Na3V2(PO4)3 or NaTi2(PO4)3 / C material layer coated on the surface of the stainless steel current collector. The negative electrode Na3V2(PO4)3 material layer includes Na3V2(PO4)3 active material, a conductive agent (carbon black C65) and a binder (PTFE). The positive electrode NaTi2(PO4)3 / C material layer includes NaTi 2(PO4)3 / C active material, conductive agent (carbon black C65) and binder (PTFE); in terms of mass percentage, Na3V2(PO4)3 accounts for 70% of the negative electrode Na3V2(PO4)3 material layer, conductive agent (carbon black C65) accounts for 20%, and binder (PTFE) accounts for 10%; in terms of mass percentage, NaTi2(PO4)3 / C accounts for 80% of the positive electrode NaTi2(PO4)3 / C material layer, conductive agent (carbon black C65) accounts for 20%, and binder (PTFE) accounts for 10%; the weight of the Na3V2(PO4)3 material layer on the negative electrode stainless steel mesh is 3.4mg, and the weight of the NaTi2(PO4)3 / C material layer on the positive electrode stainless steel mesh is 3.55mg;
[0040] like Figure 4 As shown, in this embodiment, the sulfate system electrolyte with MgSO4-K2SO4 additive added is -1 At this current density, the first discharge specific capacity of the positive electrode is 56.88 mAh g -1 The third discharge capacity is 59.44 mAh g -1 , at 0.1Ag -1 At this current density, the first discharge capacity of the negative electrode reached 38.5 mAh g -1 ; at 0.1Ag -1 At this current density, the first discharge capacity of the full battery reaches 45.07 mAh g -1 After 300 cycles, the specific capacity remains at 44.18 mAh g -1 , with high cycle stability.
[0041] Embodiment 5: A method for improving the specific capacity and stability of an aqueous sodium ion battery, using a sulfate system electrolyte, wherein the sulfate system electrolyte comprises sodium sulfate, an additive (MgSO4) and deionized water; the concentration of sodium sulfate in the sulfate system electrolyte is 2.2 mol / L, the concentration of the additive (MgSO4) is 1.14 mol / L, and the concentration of the additive (K2SO4) is 0.48 mol / L;
[0042] Taking the sulfate system electrolyte without MgSO4 as a reference and Ag / AgCl as a reference electrode, the electrochemical test was performed by linear sweep voltammetry. The electrochemical stability window of the sulfate system electrolyte without MgSO4-K2SO4 was about 3.25V, and its ion conductivity was 98.6mS / cm at room temperature; the electrochemical stability window of the sulfate system electrolyte with MgSO4-K2SO4 added in this embodiment was about 3.63V, and its ion conductivity was 85mS / cm at room temperature;
[0043] In this embodiment, the GCD curves of the positive and negative electrodes are tested by a three-electrode system, including a working electrode (the negative electrode active material is Na3V2(PO4)3, and the positive electrode active material is NaTi2(PO4)3 / C), a reference electrode (Ag / AgCl), a counter electrode (graphite carbon rod) and a sulfate system electrolyte. The working electrode includes a stainless steel current collector and a Na3V2(PO4)3 or NaTi2(PO4)3 / C material layer coated on the surface of the stainless steel current collector. The negative electrode Na3V2(PO4)3 material layer includes Na3V2(PO4)3 active material, a conductive agent (carbon black C65) and a binder (PTFE). The positive electrode NaTi2(PO4)3 / C material layer includes NaT i2(PO4)3 / C active material, conductive agent (carbon black C65) and binder (PTFE); in terms of mass percentage, Na3V2(PO4)3 accounts for 70% of the negative electrode Na3V2(PO4)3 material layer, conductive agent (carbon black C65) accounts for 20%, and binder (PTFE) accounts for 10%; in terms of mass percentage, NaTi2(PO4)3 / C accounts for 80% of the positive electrode NaTi2(PO4)3 / C material layer, conductive agent (carbon black C65) accounts for 20%, and binder (PTFE) accounts for 10%; the weight of the Na3V2(PO4)3 material layer on the negative electrode stainless steel mesh is 3.3mg, and the weight of the NaTi2(PO4)3 / C material layer on the positive electrode stainless steel mesh is 3.8mg;
[0044] In this embodiment, the sulfate electrolyte with MgSO4-K2SO4 additive is added, and the electrolyte is 0.1Ag -1 At this current density, the first discharge specific capacity of the positive electrode is 56.5 mAh g -1 The third discharge capacity is 58.7 mAh g -1 , at 0.1Ag -1 At this current density, the first discharge capacity of the negative electrode reached 38.3 mAh g -1 ; at 0.1Ag -1 At this current density, the first discharge capacity of the full battery reaches 44.9 mAh g -1 After 300 cycles, the specific capacity remains at 43.8 mAh g -1 , with high cycle stability.
[0045] Example 6: A method for improving the specific capacity and stability of an aqueous sodium ion battery, using a sulfate system electrolyte, wherein the sulfate system electrolyte comprises sodium sulfate, an additive (MgSO4) and deionized water; the concentration of sodium sulfate in the sulfate system electrolyte is 2.1 mol / L, the concentration of the additive (MgSO4) is 1.14 mol / L, and the concentration of the additive (K2SO4) is 0.5 mol / L;
[0046] Taking the sulfate system electrolyte without MgSO4 as a reference and Ag / AgCl as a reference electrode, the electrochemical test was performed by linear sweep voltammetry. The electrochemical stability window of the sulfate system electrolyte without MgSO4 was about 3.25V, and its ion conductivity was 98.6mS / cm at room temperature; the electrochemical stability window of the sulfate system electrolyte with MgSO4 added in this embodiment was about 3.64V, and its ion conductivity was 85.6mS / cm at room temperature;
[0047] In this embodiment, the GCD curves of the positive and negative electrodes are tested by a three-electrode system, including a working electrode (the negative electrode active material is Na3V2(PO4)3, and the positive electrode active material is NaTi2(PO4)3 / C), a reference electrode (Ag / AgCl), a counter electrode (graphite carbon rod) and a sulfate system electrolyte. The working electrode includes a stainless steel current collector and a Na3V2(PO4)3 or NaTi2(PO4)3 / C material layer coated on the surface of the stainless steel current collector. The negative electrode Na3V2(PO4)3 material layer includes Na3V2(PO4)3 active material, a conductive agent (carbon black C65) and a binder (PTFE). The positive electrode NaTi2(PO4)3 / C material layer includes NaT i2(PO4)3 / C active material, conductive agent (carbon black C65) and binder (PTFE); in terms of mass percentage, Na3V2(PO4)3 accounts for 70% of the negative electrode Na3V2(PO4)3 material layer, conductive agent (carbon black C65) accounts for 20%, and binder (PTFE) accounts for 10%; in terms of mass percentage, NaTi2(PO4)3 / C accounts for 80% of the positive electrode NaTi2(PO4)3 / C material layer, conductive agent (carbon black C65) accounts for 20%, and binder (PTFE) accounts for 10%; the weight of the Na3V2(PO4)3 material layer on the negative electrode stainless steel mesh is 3.6 mg, and the weight of the NaTi2(PO4)3 / C material layer on the positive electrode stainless steel mesh is 4.6 mg;
[0048] In this embodiment, the sulfate electrolyte with MgSO4-K2SO4 additive is added, and the electrolyte is 0.1Ag -1 At this current density, the first discharge specific capacity of the positive electrode is 56.7 mAh g -1 The third discharge capacity is 58.9 mAh g -1 , at 0.1Ag -1 At this current density, the first discharge capacity of the negative electrode reached 38.7 mAh g -1 ; at 0.1Ag -1 At this current density, the first discharge capacity of the full battery reaches 44.7 mAh g -1 After 300 cycles, the specific capacity remains at 43.6 mAh g -1 , with high cycle stability.
[0049] Embodiment 7: A method for improving the specific capacity and stability of an aqueous sodium ion battery, using a sulfate system electrolyte, wherein the sulfate system electrolyte comprises sodium sulfate, an additive (MgSO4-(NH4)2SO4 mixed additive) and deionized water; the concentration of sodium sulfate in the sulfate system electrolyte is 2.2 mol / L, the concentration of the additive (MgSO4) is 1.2 mol / L, and the concentration of the additive ((NH4)2SO4) is 0.46 mol / L;
[0050] Taking the sulfate system electrolyte without adding MgSO4-(NH4)2SO4 as a reference and Ag / AgCl as a reference electrode, the electrochemical test was carried out by linear sweep voltammetry. The electrochemical stability window of the sulfate system electrolyte without adding the MgSO4-(NH4)2SO4 mixed additive was about 3.25V, and its ion conductivity was 98.6mS / cm at room temperature; the electrochemical stability window of the sulfate system electrolyte with the MgSO4-(NH4)2SO4 mixed additive added in this embodiment was about 3.45V, and its ion conductivity was 87.8mS / cm at room temperature;
[0051] In this embodiment, the GCD curves of the positive and negative electrodes are tested by a three-electrode system, including a working electrode (the negative electrode active material is Na3V2(PO4)3, and the positive electrode active material is NaTi2(PO4)3 / C), a reference electrode (Ag / AgCl), a counter electrode (graphite carbon rod) and a sulfate system electrolyte. The working electrode includes a stainless steel current collector and a Na3V2(PO4)3 or NaTi2(PO4)3 / C material layer coated on the surface of the stainless steel current collector. The negative electrode Na3V2(PO4)3 material layer includes Na3V2(PO4)3 active material, a conductive agent (carbon black C65) and a binder (PTFE). The positive electrode NaTi2(PO4)3 / C material layer includes NaT i2(PO4)3 / C active material, conductive agent (carbon black C65) and binder (PTFE); in terms of mass percentage, Na3V2(PO4)3 accounts for 70% of the negative electrode Na3V2(PO4)3 material layer, conductive agent (carbon black C65) accounts for 20%, and binder (PTFE) accounts for 10%; in terms of mass percentage, NaTi2(PO4)3 / C accounts for 80% of the positive electrode NaTi2(PO4)3 / C material layer, conductive agent (carbon black C65) accounts for 20%, and binder (PTFE) accounts for 10%; the weight of the Na3V2(PO4)3 material layer on the negative electrode stainless steel mesh is 3.4mg, and the weight of the NaTi2(PO4)3 / C material layer on the positive electrode stainless steel mesh is 3.7mg;
[0052] In this embodiment, the sulfate electrolyte with MgSO4-(NH4)2SO4 additive is added, and the electrolyte is 0.1Ag -1 At this current density, the first discharge specific capacity of the positive electrode is 57.7 mAh g-1 The third discharge capacity is 60.9 mAh g -1 , at 0.1Ag -1 At this current density, the first discharge capacity of the negative electrode reached 39.7 mAh g -1 ; at 0.1Ag -1 At this current density, the first discharge capacity of the full battery reaches 47 mAhg -1 After 300 cycles, the specific capacity remains at 45 mAhg -1 , with high cycle stability.
[0053] Embodiment 8: A method for improving the specific capacity and stability of an aqueous sodium ion battery, using a sulfate system electrolyte, wherein the sulfate system electrolyte comprises sodium sulfate, an additive (MgSO4-(NH4)2SO4 mixed additive) and deionized water; the concentration of sodium sulfate in the sulfate system electrolyte is 2.3 mol / L, the concentration of the additive (MgSO4) is 1.24 mol / L, and the concentration of the additive ((NH4)2SO4) is 0.48 mol / L;
[0054] Taking the sulfate system electrolyte without adding MgSO4-(NH4)2SO4 as a reference and Ag / AgCl as a reference electrode, the electrochemical test was carried out by linear sweep voltammetry. The electrochemical stability window of the sulfate system electrolyte without adding the MgSO4-(NH4)2SO4 mixed additive was about 3.25V, and its ion conductivity was 98.6mS / cm at room temperature; the electrochemical stability window of the sulfate system electrolyte with the addition of the MgSO4-(NH4)2SO4 mixed additive in this embodiment was about 3.48V, and its ion conductivity was 88mS / cm at room temperature;
[0055] In this embodiment, the GCD curves of the positive and negative electrodes are tested by a three-electrode system, including a working electrode (the negative electrode active material is Na3V2(PO4)3, and the positive electrode active material is NaTi2(PO4)3 / C), a reference electrode (Ag / AgCl), a counter electrode (graphite carbon rod) and a sulfate system electrolyte. The working electrode includes a stainless steel current collector and a Na3V2(PO4)3 or NaTi2(PO4)3 / C material layer coated on the surface of the stainless steel current collector. The negative electrode Na3V2(PO4)3 material layer includes Na3V2(PO4)3 active material, a conductive agent (carbon black C65) and a binder (PTFE). The positive electrode NaTi2(PO4)3 / C material layer includes NaT i2(PO4)3 / C active material, conductive agent (carbon black C65) and binder (PTFE); in terms of mass percentage, Na3V2(PO4)3 accounts for 70% of the negative electrode Na3V2(PO4)3 material layer, conductive agent (carbon black C65) accounts for 20%, and binder (PTFE) accounts for 10%; in terms of mass percentage, NaTi2(PO4)3 / C accounts for 80% of the positive electrode NaTi2(PO4)3 / C material layer, conductive agent (carbon black C65) accounts for 20%, and binder (PTFE) accounts for 10%; the weight of the Na3V2(PO4)3 material layer on the negative electrode stainless steel mesh is 3.3mg, and the weight of the NaTi2(PO4)3 / C material layer on the positive electrode stainless steel mesh is 3.4mg;
[0056] In this embodiment, the sulfate electrolyte with MgSO4-(NH4)2SO4 additive is added, and the electrolyte is 0.1Ag -1 At this current density, the first discharge specific capacity of the positive electrode is 57.8 mAh g -1 The third discharge capacity is 61 mAhg -1 , at 0.1Ag -1 At this current density, the first discharge capacity of the negative electrode reached 39.8 mAh g -1 ; at 0.1Ag -1 At this current density, the first discharge capacity of the full battery reaches 47.01 mAh g -1 After 300 cycles, the specific capacity remains at 45.2 mAh g -1 , with high cycle stability.
[0057] Embodiment 9: A method for improving the specific capacity and stability of an aqueous sodium ion battery, using a sulfate system electrolyte, wherein the sulfate system electrolyte comprises sodium sulfate, an additive (MgSO4-(NH4)2SO4 mixed additive) and deionized water; the concentration of sodium in the sulfate system electrolyte is 2.3 mol / L, the concentration of the additive (MgSO4) is 1 mol / L, and the concentration of the additive ((NH4)2SO4) is 0.5 mol / L;
[0058] Using the sulfate electrolyte without MgSO4-(NH4)2SO4 as reference and Ag / AgCl as reference electrode, electrochemical tests were performed by linear sweep voltammetry. Figure 6 As shown, the electrochemical stability window of the sulfate system electrolyte without the addition of the MgSO4-(NH4)2SO4 mixed additive is about 3.25V, and its ion conductivity is 98.6mS / cm at room temperature; the electrochemical stability window of the sulfate system electrolyte with the addition of the MgSO4-(NH4)2SO4 mixed additive in this embodiment is about 3.38V, and its ion conductivity is 88mS / cm at room temperature;
[0059] In this embodiment, the GCD curves of the positive and negative electrodes are tested by a three-electrode system, including a working electrode (the negative electrode active material is Na3V2(PO4)3, and the positive electrode active material is NaTi2(PO4)3 / C), a reference electrode (Ag / AgCl), a counter electrode (graphite carbon rod) and a sulfate system electrolyte. The working electrode includes a stainless steel current collector and a Na3V2(PO4)3 or NaTi2(PO4)3 / C material layer coated on the surface of the stainless steel current collector. The negative electrode Na3V2(PO4)3 material layer includes Na3V2(PO4)3 active material, a conductive agent (carbon black C65) and a binder (PTFE). The positive electrode NaTi2(PO4)3 / C material layer includes NaT i2(PO4)3 / C active material, conductive agent (carbon black C65) and binder (PTFE); in terms of mass percentage, Na3V2(PO4)3 accounts for 70% of the negative electrode Na3V2(PO4)3 material layer, conductive agent (carbon black C65) accounts for 20%, and binder (PTFE) accounts for 10%; in terms of mass percentage, NaTi2(PO4)3 / C accounts for 80% of the positive electrode NaTi2(PO4)3 / C material layer, conductive agent (carbon black C65) accounts for 20%, and binder (PTFE) accounts for 10%; the weight of the Na3V2(PO4)3 material layer on the negative electrode stainless steel mesh is 3.3mg, and the weight of the NaTi2(PO4)3 / C material layer on the positive electrode stainless steel mesh is 3.5mg;
[0060] like Figure 7 As shown, in this embodiment, the sulfate system electrolyte with MgSO4-(NH4)2SO4 additive is added, at 0.1Ag -1 At this current density, the first discharge specific capacity of the positive electrode is 57.3 mAh g -1 The third discharge capacity is 58.6 mAh g -1 , at 0.1Ag -1 At this current density, the first discharge capacity of the negative electrode reached 39.4 mAh g -1 ; at 0.1Ag -1At this current density, the first discharge capacity of the full battery reaches 45.01 mAh g -1 After 300 cycles, the specific capacity remains at 44.15 mAh g -1 , with high cycle stability.
[0061] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.
Claims
1. A method for improving the specific capacity and stability of an aqueous sodium ion battery, characterized in that: A sulfate system electrolyte is used, wherein the sulfate system electrolyte comprises sodium sulfate, an additive and deionized water, wherein the additive is MgSO4, a MgSO4-K2SO4 mixed additive or a MgSO4-(NH4)2SO4 mixed additive; The sodium sulfate concentration in the sulfate system electrolyte is 2-2.3 mol / L.
2. The method for improving the specific capacity and stability of an aqueous sodium ion battery according to claim 1, characterized in that: When the additive is MgSO4, the concentration of the additive MgSO4 is 1-1.24 mol / L.
3. The method for improving the specific capacity and stability of an aqueous sodium ion battery according to claim 1, characterized in that: When the additive is a MgSO4-K2SO4 mixed additive, the concentration of the additive MgSO4 is 1-1.24 mol / L, and the concentration of K2SO4 is 0.46-0.5 mol / L.
4. The method for improving the specific capacity and stability of an aqueous sodium ion battery according to claim 1, characterized in that: When the additive is a MgSO4-(NH4)2SO4 mixed additive, the concentration of the additive MgSO4 is 1-1.24 mol / L, and the concentration of (NH4)2SO4 is 0.46-0.5 mol / L.
5. The method for improving the specific capacity and stability of an aqueous sodium ion battery according to claim 1, characterized in that: The electrochemical stability window of the sulfate system electrolyte is 3.2-3.67V, and the conductivity value is 77.3-98.6mS / cm.
6. The method for improving the specific capacity and stability of an aqueous sodium ion battery according to claim 1, characterized in that: The negative electrode material of the aqueous sodium ion battery is a titanium-based polyanion compound NaTi2(PO4)3 / C, and the positive electrode material is a vanadium-based polyanion compound Na3V2(PO4)3.